International Teaching Assistants and teacher identity. Issue 2 (25th August 2015) - LoCastro, Virginia; Tapper, Gordon
Abstract : This paper reports on a study of International Teaching Assistant (ITA) teacher identity construction at a U.S. tertiary institution, an example of an 'atypical' research site neglected by the current perspective of Western dominated applied linguistics. The researchers adopt a critical perspective to explore complex micro classroom interactions as well as macro dimensions of the D/discourses woven intertextually into introductory courses in sciences and business. The study focuses in particular on the educational function ITAs perform as NNE speaker teachers, the extent of their accommodation to U.S. pedagogical norms, and the construction of their identities as expert teachers. Video taped classroom sessions as well as interviews and retrospective accounts of five participants comprise rich data for 23 extracts of talk and discussion of ITA pedagogical practices, challenges and conflicts, and attitudes towards negotiation of U.S. norms and their own teacher identities. This interview-based case study raises issues related to teacher training of both ITAs and NE speaker teaching assistants, the role of NNE speakers as sources of diversity and multiculturalism, and the need for increased awareness of U.S. institutions of world Englishes and movement away from the deficit view of international teaching personnel so often observed.